Thickness Optimization of Highly Porous Flame-Aerosol Deposited WO(3) Films for NO(2) Sensing at ppb - Abegg, Sebastian (Nanomaterials (Basel), 2020)
Nitrogen dioxide (NO(2)) is a major air pollutant resulting in respiratory problems, from wheezing, coughing, to even asthma. Low-cost sensors based on WO(3) nanoparticles are promising due to their distinct selectivity to detect NO(2) at the ppb level. Here, we revealed that controlling the thickness of highly porous (97%) WO(3) films between 0.5 and 12.3 μm altered the NO(2) sensitivity by more than an order of magnitude. Therefore, films of WO(3) nanoparticles (20 nm in diameter by N(2) adsorption) with mixed γ- and ε-phase were deposited by single-step flame spray pyrolysis without affecting crystal size, phase composition, and film porosity. That way, sensitivity and selectivity effects were associated unambiguously to thickness, which was not possible yet with other sensor fabrication methods. At the optimum thickness (3.1 μm) and 125 °C, NO(2) concentrations were detected down to 3 ppb at 50% relative humidity (RH), and outstanding NO(2) selectivity to CO, methanol, ethanol, NH(3) (all > 10(5)), H(2), CH(4), acetone (all > 10(4)), formaldehyde (>10(3)), and H(2)S (835) was achieved. Such thickness-optimized and porous WO(3) films have strong potential for integration into low-power devices for distributed NO(2) air quality monitoring.